The application of the method of laser doppler flowmetry to assess microcirculation in obstetric-gynecological pathology - P. H. Gadzhieva; L. V. Dikareva; O. S. Polunina; L. P. Voronina; I. Z. Davydova; O. M. Denisova (Кубанский научный медицинский вестник, 2016)
Smoking is one of the most pressing public health problems. Despite numerous antismoking campaigns, the proportion of women smokers is not decreasing. Smoking during pregnancy has an adverse influence on the physiological course of pregnancy and on the fetus and newborn. It has been proven that tobacco smoke is detected about 4 thousand different chemical compounds, of which 200 are the most toxic. Therefore the fetus develops in conditions of chronic hypoxia and is subjected to a toxic effect of constituents of tobacco smoke. In this connection there is a need to investigate the condition of the skin microcirculation with early pregnancy. At the present time, wide implementation in practice of doctors of various specialties, including obstetricians and gynecologists, the method of laser doppler flowmetry.